PENGARUH KUALITAS BARANG, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Salsabila, Farah; Sudiro, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Kalome is a micro, small, and medium-sized enterprise in Malang that sells aromatic candle. This product started to be high in demand in the beginning of 2020 during the Covid-19 pandemic as it helps people sleep well and remove stress. However, its sales in Malang are lower than other major cities such as Yogyakarta. In order to achieve high purchase decision, goods must be reliable and good in quality, priced according to its usefulness and quality, promoted in the correct method. The objective of this research is to identify the influence magnitude of goods quality, price, and promotion on purchase decision, the influence magnitude of goods quality on the purchase decision, the influence magnitude of price on the purchase decision, and the influence magnitude of promotion on the purchase decision. The sample of this quantitative descriptive research is 65 consumers of Kalome therapeutical aromatic candle in Malang area, selected using purposive sampling technique. The data was analyzed using multiple linear regression, coefficient of determination, and hypothesis testing. This research finds that goods quality, price, and promotion simultaneously have significant impact on the purchase decision. Partially, goods quality significantly influences the purchase decision, and price significantly affects the purchase decision, while promotion has no significant influence on the purchase decision.